1984
DOI: 10.5271/sjweh.2323
|View full text |Cite
|
Sign up to set email alerts
|

Skin absorption as a source of error in biological monitoring.

Abstract: , MD1AITIO A, PEKARI K, JARVISALO J. Skin absorption as a source of error in biological monitoring. Scand J Work Environ Health 10 (1984) 317-320. Concentrations of toluene, tetrachloroethylene, and l,l,l-trichloroethane were determined in blood collected from both forearms of subjects after one of their hands was soaked for 5 min in the corresponding solvent or in a thinner containing toluene, as a simulation of the washing of hands with solvent after work. The concentrations of toluene, tetrachloroethylene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Traditionally, industrial hygienists have paid attention to inhalation hazards, because it was thought to be the major exposure route; however, Lees et al (1987) reported that the dermal route was the major contributor to total body burden of polychlorinated biphenyls in some occupational settings. Aitio et al (1984) reported skin absorption was also an exposure source in biological monitoring. Daniell et al (1992) indicated that hand contact with liquid xylene for 15 min resulted in the absorbed dose exceeding that obtained from inhalation over a full 8-h shift in motor repair shop workers.…”
Section: Discussionmentioning
confidence: 97%
“…Traditionally, industrial hygienists have paid attention to inhalation hazards, because it was thought to be the major exposure route; however, Lees et al (1987) reported that the dermal route was the major contributor to total body burden of polychlorinated biphenyls in some occupational settings. Aitio et al (1984) reported skin absorption was also an exposure source in biological monitoring. Daniell et al (1992) indicated that hand contact with liquid xylene for 15 min resulted in the absorbed dose exceeding that obtained from inhalation over a full 8-h shift in motor repair shop workers.…”
Section: Discussionmentioning
confidence: 97%
“…Specific strategies for the sampling of biological fluids may be necessary. Furthermore, the position of blood sampling relative to the skin exposure may be critical for the outcome, 4 and possible skin metabolism is not generally taken into consideration. 5 No quantitative limit values exist that may protect against adverse eVects from uptake through dermal exposure.…”
mentioning
confidence: 99%
“…Previous studies reported that painters used to wash their contaminated skin with solvents, and skin absorption is a source of error in biological monitoring. [15][16][17] In our study, the workers did not wash their skin with solvents. The source of the dermal contact was the deposition of paint aerosol on the skin and the uptake of solvent vapor.…”
Section: Discussionmentioning
confidence: 94%